Kontribusi kepercayaan diri dan efikasi diri akademik terhadap nilai mata kuliah statistik inferensial - Farid Imam Kholidin; Indriyana Rachmawati; Eko Pramudya Laksana (Research and Social Study Institute, 2020)
Tujuan dari penelitian ini adalah untuk: mengidentifikasi kontribusi simultan dari kepercayaan diri akademik dan self-efficacy akademik ke nilai akhir matakuliah Statistik Inferensial; mengidentifikasi kontribusi parsial kepercayaan diri akademik ke nilai akhir matakuliah Statistik Inferensial; mengidentifikasi kontribusi parsial dari self-efficacy akademik ke nilai akhir matakuliah Statistik Inferensial; dan mengidentifikasi kontribusi kepercayaan diri akademik dan self-efficacy akademik pada nilai akhir matakuliah Statistik Inferensial. Penelitian ini menggunakan kuantitatif. Hasil penelitian menunjukkan bahwa: ada kontribusi simultan kepercayaan diri akademik dan self-efficacy akademik padanilai akhir matakuliah Statistik Inferensial; belum ada kontribusi parsial kepercayaan diri akademik pada nilai akhir matakuliah Statistik Inferensial; ada kontribusi parsial dari self-efficacy akademik pada nilai akhir matakuliah Statistik Inferensial; dan kontribusi kepercayaan diri akademik dan self-efficacy akademik untuk nilai akhir kursus Statistik Inferensial sebesar 42,90%. Contribution of self-confidence and academic self-efficacy to students' final semester grade AbstractThe objectives of the study were to: identify the simultaneous contribution of academic self-confidence and academic self-efficacy to the final grade of Inferential Statistics course; identify the partial contribution of academic self-confidence to the final grade of Inferential Statistics course; identify the partial contribution of academic self-efficacy to the final grade of Inferential Statistics course; and identify the contribution size of academic self-confidence and academic self-efficacy to the final grade of Inferential Statistics course. In conducting the study, the quantitative method was implemented. Results showed that: there has been simultaneous contribution of academic self-confidence and academic self-efficacy to the final grade of Inferential Statistics course; there has not been partial contribution of academic self-confidence to the final grade of Inferential Statistics course; there has been partial contribution of academic self-efficacy to the final grade of Inferential Statistics course; and the contribution of academic self-confidence and academic self-efficacy to the final grade of Inferential Statistics course has been 42.90%.